BEHAVIOR OF PHYSIOLOGICAL VARIABLE DURING THE HIDROGIMNASTIC CLASS (Fiep Bulletin - online, 2014)
Hidrogymnastic practice has increased considerably, because it can be used to help rehabilitation as well as to increase physical conditioning. However, no works about physiological variables behavior are found in literature, becoming emergent to analyze HR and VO2 behavior during aerobic phase of a hidrogymnastic class. 12 undergraduate students were studied (age of 23,43±4,08, stature of 174,75±6,47cm, 73,28±8,36kg and %GC of 12,42±4,09) in two different stages. In stage 1, an ergoespirometric test in rolling mat was done (Mader´s protocol) and in stage 2 was realized a corporal evaluation and also a hidrogymnastic class in the temperature of 32±0,5oC and the depth of the water was adequated to xifoid process. HR (oftener, Polar mark) and VO2 (gas analyst Aerosport TEEM100) were gotten each 20 seconds. In accordance with the gotten results, 75% (in relation to HR) and 67% (in relation to VO2) of the investigated people presented satisfactory values in general average during the aerobic phase of the class. The analysis of the different groups showed that for the first two, %HRmax average remained below of the limit stipulated by literature, as well as to %VO2peak during group 1 exercises. Groups 3, 4, 5 and 6 presented intensity results adjusted to the improvement of cardiorespiratory aptitude. It was concluded that the methodology applied in the studied class is enough to the improvement of undergraduate students´ cardiorespiratory aptitude. Despite that, the results from each group showed that is possible to project, through this methodology, different classes for this group of people, providing alternatives for hidrogymnastic, helping in this way  professionals of the area in their practice.
Keywords: Hidrogimnastic Class; Heart Rate; Oxygen Consumption